Essentials of Victimology: Crime Victims, Theories, Controversies, and Victims' Rights - Yager, Jan (Aspen Criminal Justice Ser., 2021)
Intro -- Front Matter -- Editorial Advisors -- Title Page -- Copyright -- About Wolters Kluwer Legal &amp -- Regulatory U.S. -- Dedication -- Brief Contents -- Detailed Contents -- Preface -- Chapter One: Victimology: An Overview -- Learning Objectives -- Defining Victimology -- Who Are the Victims? -- Putting Victimology in a Historical Context -- Primary, Secondary, Tertiary, and Quaternary Victims -- Categories of Crimes and Victims -- What Victimologists Might Study -- Ten Reasons to Study Victimology -- Some Questions to Consider -- Summary -- Key Terms -- Review Questions -- Critical Thinking Questions -- Activities -- Resources -- Cited Works and Additional References -- Videos, Documentaries, and Films -- Chapter Two: An Anthropological and Historical View of Crime Victims and Victims' Rights -- Learning Objectives -- How a Victim's Justice System Evolved into Today's Criminal Justice System -- A Cross-Cultural View of Crime Victims -- Recap: The Victim in Primitive Cultures -- A Historical View of Crime Victim Treatment in Public Law -- When Crime Became a Public Wrong -- The History of Crime Victims in the United States -- Victims' Rights -- Summary -- Key Terms -- Review Questions -- Critical Thinking Questions -- Activities -- Resources -- Cited Works and Additional References -- Videos, Films, Documentaries, and Podcasts -- Chapter Three: The Discipline of Victimology: Founders, Theories, and Controversies -- Learning Objectives -- Earliest Roots of Victimology -- Victimology Founders and Their Theories: Typologies -- Empirical Victim Studies -- The Victim Finally Takes Center Stage -- The Next Generation of Theories: An Opportunity Approach -- Additional Victimology Theories -- Three Basic Perspectives in Victimology -- Applying Sutherland's Learning Theory of Deviance to Crime Victims.